Ocorrência de podridão negra, causada por Chalara elegans, em raízes de cenoura no Rio Grande do Sul - Dalbosco, Marisa (2004)
Ocurrence of black root, caused of Chalara elegans, in carrot rot in the State of Rio Grande do Sul A black root rot in carrot (Daucus carotae), caused by Chalara elegans, is reported for the first time in the State of Rio Grande do Sul, Brazi